Adiposity Alters Genes Important in Inflammation and Cell Cycle Division in Human Cumulus Granulosa Cell. (October 2015) - Merhi, Zaher; Polotsky, Alex J.; Bradford, Andrew P.; Buyuk, Erkan; Chosich, Justin; Phang, Tzu; Jindal, Sangita; Santoro, Nanette
Objective: To determine whether obesity alters genes important in cellular growth and inflammation in human cumulus granulosa cells (GCs). Methods: Eight reproductive-aged women who underwent controlled ovarian hyperstimulation followed by oocyte retrieval for in vitro fertilization were enrolled. Cumulus GC RNA was extracted and processed for microarray analysis on Affymetrix Human Genome U133 Plus 2.0 chips. Gene expression data were validated on GCs from additional biologically similar samples using quantitative real-time polymerase chain reaction (RT-PCR). Comparison in gene expression was made between women with body mass index (BMI) <25 kg/m 2 (group 1; n = 4) and those with BMI ≥25 kg/m 2 (group 2; n = 4). Results: Groups 1 and 2 had significantly different BMI (21.4 ± 1.4 vs 30.4 ± 2.7 kg/m 2, respectively; P = .02) but did not differ in age (30.5 ± 1.7 vs 32.7 ± 0.3 years, respectively; P = .3). Comparative analysis of gene expression profiles by supervised clustering between group 1 versus group 2 resulted in the selection of 7 differentially expressed genes: fibroblast growth factor 12 (FGF-12), protein phosphatase 1-like (PPM1L), zinc finger protein multitype 2 (ZFPM2), forkhead box M1 (FOXM1), cell division cycle 20 (CDC20), interleukin 1 receptor-like 1 (IL1RL1), and growth arrest-specific protein 7 (GAS7). FOXM1, CDC20, and GAS7 were downregulated while FGF-12 and PPM1L were upregulated in group 2 when compared to group 1. Validation with RT-PCR confirmed the microarray data except for ZFPM2 and IL1RL. As BMI increased, expression of FOXM1 significantly decreased ( r = −.60, P = .048). Conclusions: Adiposity is associated with changes in the expression of genes important in cellular growth, cell cycle progression, and inflammation. The upregulation of the metabolic regulator gene PPM1L suggests that adiposity induces an abnormal metabolic follicular environment, potentially altering folliculogenesis and oocyte quality.